Antimalarial activity of piperidine alkaloids from Senna spectabilis and semisynthetic derivatives - Pivatto, Marcos; Baccini, Luciene R. [UNESP]; Sharma, Abhinay; Nakabashi, Myna; Danuello, Amanda; Viegas Júnior, Claudio; Garcia, Celia R. S.; Bolzani, Vanderlan da Silva [UNESP] (Sociedade Brasileira de Química, 2014)
In our continuing work looking for new anti-infective lead compounds from Brazilian biomes, the two known piperidine alkaloids ( - )-cassine and ( - )-spectaline were isolated from the flowers of Senna spectabilis (syn. Cassia spectabilis). Their structures were elucidated using a combination of spectroscopic and spectrometric data analysis. Further, these compounds were acetylated yielding the derivatives ( - )-3-O-acetylcassine and ( - )-3-O-acetylspectaline. All compounds were screened against P. falciparum-infected red blood cells (RBC) in culture, aiming to identify antimalarial prototypes. Among all compounds screened, the first two alkaloids (IC50 1.82 µM and IC50 2.76 µM) were more effective than the derivatives (IC50 24.47 µM and IC50 25.14 µM) in comparison to the standard compound chloroquine (IC50 0.30 µM). These data show that piperidine alkaloids constitute a class of natural products that feature a broad spectrum of biological activities, and are, therefore, important templates for drug design, including antimalarial.

Dando continuidade as pesquisas de identificação de metabólitos secundários com propriedades anti-infecciosas potenciais a partir de espécies de plantas dos biomas brasileiros, dois alcaloides piperidínicos ( - )-cassina e ( - )-espectalina foram isolados das flores de Senna spectabilis (sin. Cassia spectabilis). As estruturas destes compostos foram elucidadas a partir de dados espectroscópicos e espectrométricos. Adicionalmente, esses alcaloides foram acetilados, resultando nos derivados ( - )-3-O-acetilcassina e ( - )-3-O-acetilespectalina. Todas as substâncias foram submetidas ao bioensaio empregando culturas de eritrócitos, infectadas com Plasmodium falciparum, um teste específico para avaliação antimalárica. Dentre as substâncias avaliadas, os dois primeiros alcaloides (IC50 1,82 µM e IC50 2,76 µM) foram mais potentes que os derivados (IC50 24,47 µM e IC50 25,14 µM) em comparação com a cloroquina (IC50 0,30 µM), utilizada como padrão. Estes dados mostram que os alcaloides piperidínicos constituem uma classe de produtos naturais que apresenta amplo espectro de atividades biológicas, sendo portanto, importantes modelos para o planejamento de fármacos, incluindo os antimaláricos.
Keywords: piperidine alkaloids; Senna spectabilis; semisynthetic derivatives; antimalarial activity; Plasmodium falciparum